Consumer purchase decision towards canned pineapple products: a case study in Malacca / Rafidah A.Raof - A.Raof, Rafidah (2018)
Nowadays, people are more particular and concern about their food taken daily which mean their attitude has emerged in today’s modern world due to increase in awareness of the importance to maintain a healthy lifestyle without consuming a food with unsafe additives. Moreover, the influx of technology, advertising, images in the media and changes within modern cultural and family Values play a big role in the psychological evolution of consumers in the food service industry. Thus, this study attempted to investigate factors influencing consumer’s purchase decision towards canned pineapple products in Malacca‘ A study of 200 purchasers of canned pineapple products in hypermarket was conducted throughout the survey method using a structured questionnaire, with close-ended questions. The convenience sampling technique was applied to obtain responses from the purchasers of canned pineapple products in hypermarket. It was decided to use a various multivariate analyses like exploratory factor analysis (EFA), independent t-test analysis, one-way analysis of variance (ANOVA) and multiple regression analysis. The conceptual framework for this study was derived from the abstract ideas of the Theory of Flamed Behaviour. Accordingly, factors such as subjective norms from the original theory also included with an added independent variables (labelling, prior knowledge, perceived value, and consumer’s lifestyle), to understand its impact on consumer’s purchase decision toward canned pineapple products. The results reveal that labelling, perceive value and consumer’s lifestyle have significant relationship with consumer’s purchase decision towards canned pineapple products in Malacca. The results also indicate that only profile respondent of race, occupation and level of concern about nutrient loss that have significant difference with variables tested‘ Moreover, this study found out the most dominant of consumer’s purchasing decision towards canned pineapple products are consumer’s lifestyle. The transformation happening in our food sector makes it crucial to understand the consumption patterns and their underlying determinants for canned food product‘ In fact, consumer’s perception and level of understanding consumer towards canned food product industry also were limitation in this study.